Linking diversity to organizational effectiveness: Lessons from a culture study at CIAT - Amariles, F.; Peralta, G.; Johnson, Nancy L. (2006)
This Brief describes a ‘culture study’ carried out to explore how different staff groups perceive the culture of an international research centre and how the management of staff diversity issues affects the work environment and organizational performance. The perceptions of various staff groups were analysed in relation to five aspects of organizational culture: institutional climate; global competitiveness; empowerment and group motivation; work–life balance; and equity in gender and diversity. The study identified what staff believed to be the key strengths and weaknesses in the organization’s culture and detected four strategic areas for improvement: internal organizational communications; re-design of job positions and responsibilities; multi-cultural competencies; and gender awareness in the workplace. The diagnostic process is described, as well as the follow-up actions taken to improve the management of gender and diversity in the centre.